Adaptation and validation of the Persian version of the foot Health Status Questionnaire in patients with plantar pain: evaluation of test-retest - Ahmadnezhad, Leila; López-López, Daniel; Becerro-de-Bengoa-Vallejo, Ricardo; Jiménez-Cebrián, Ana María; Losa-Iglesias, Marta Elena; Casado Hernández, Israel; Alves-Gomes, Lisa; Navarro-Flores, Emmanuel María (Taylor & Francis, 2025)
Background: The Foot Health Status Questionnaire (FHSQ) is a foot health psychometric tool for measuring foot health status that consists of eight dimensions. Currently, the FHSQ has been adapted to several languages. It was considered necessary to translate and adapt the FHSQ to the Persian language. Thus, the aim of this study was to assess the repeatability and reliability of the Foot Health Status Questionnaire (FHSQ) translated into Persian. Method: The translation into Persian and test-retest reliability methods came from the English version of the questionnaire. The questionnaire was distributed to 88 individuals diagnosed with plantar heel pain, who were recruited from a podiatry clinic in Iran. To assess test-retest reliability, the instrument was administered on two separate occasions, with a five-day interval between the initial and follow-up assessments. Results: As regards the total mark for each dimension, internal consistency and reliability were determined with the Cronbach α and intraclass correlation coefficient (ICC) with a confidence interval (CI) of 95%. High internal consistency was shown for the eight dimensions: (a) foot pain, with a Cronbach α of 0.773; (b) foot function and (c) general foot health with 0.788 and 0.776 respectively; (d) shoe with 0.793; (e) general health with 0.784; (f) physical function with 0.795; (g) social function with 0.801 and (h) vigour with 0.748. Excellent test-retest reliability (ICC = 0.911 [95% CI =0.844–0.949]) was shown for the total score. Conclusions: The Persian version of the FHSQ was shown to be a valid and reliable tool for acceptable use in the Iran population.
Keywords: Pies - Enfermedades - Tratamiento; Valoración de enfermería; Foot health status questionnaire; Foot health; Quality of life; Reliability analysis; Questionnaire validation